PENGARUH KUALITAS PELAYANAN DAN FASILITAS RESTORAN TERHADAP KEPUASAN PENUMPANG PADA KERETA API SEMBRANI - Syahmaulana, Asep Riendi; Wahyudi, Dedy; Zuhrofi , Ahmad (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to analyze the influence of service quality and restaurant facilities on passenger satisfaction on the Sembrani Train. The research involved 100 respondents selected using the probability sampling method with purposive sampling technique. Data were analyzed using the t-test, which revealed that service quality and restaurant facilities have a positive and significant influence on passenger satisfaction. Among the variables analyzed, service quality has a more dominant impact compared to restaurant facilities in determining passenger satisfaction. Simultaneously, service quality and restaurant facilities have a positive and significant impact on passenger satisfaction. This research is expected to provide valuable insights for business practitioners, particularly PT KAI, in enhancing passenger satisfaction on the Sembrani Train.